ChemInform Abstract: Holophyllin A, a Rearranged Abietane‐Type Diterpenoid from the Trunk of Abies holophylla. Issue 17 (April 2015) - Kim, Chung Sub; Shin, Bora; Kwon, Oh Wook; Kim, Sun Yeou; Choi, Sang Un; Oh, Dong‐Chan; Kim, Ki Hyun; Lee, Kang Ro
Abstract Holophyllin A (I) and the new diterpene glycoside homophyllin B (II) are isolated from the trunk of Abies holophylla.